2021
DOI: 10.1016/j.jiac.2020.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Could threshold cycle value correctly reflect the severity of novel coronavirus disease 2019 (COVID-19)?

Abstract: The novel coronavirus disease 2019 (COVID-19) is diagnosed by positive result of reverse transcription polymerase chain reaction (RT-PCR) for the novel coronavirus. We concluded that cycle threshold value (Ct-value) of real-time RT-PCR (rRT-PCR) assay could decrease as patients recover. Results of rRT-PCR assay could remain positive among asymptomatic patients for longer than 2 weeks. The discharge criteria of COVID-19 patients using a negative result of rRT-PCR should be reconsidered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…We previously reported that 47% of COVID-19 pneumonia patients were asymptomatic, even when radiological findings on chest CT were confirmed [3]. The severity of COVID-19 could be correlated with the viral load as well as the Ct-value of RT-PCR [12,13]. Patients who show a high antigen level of the automated quantitative CLEIA antigen test should receive a chest CT scan, particularly those with underlying disease.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that 47% of COVID-19 pneumonia patients were asymptomatic, even when radiological findings on chest CT were confirmed [3]. The severity of COVID-19 could be correlated with the viral load as well as the Ct-value of RT-PCR [12,13]. Patients who show a high antigen level of the automated quantitative CLEIA antigen test should receive a chest CT scan, particularly those with underlying disease.…”
Section: Discussionmentioning
confidence: 99%
“…This was surprising, considering the published high rates of mortality in this age group. However, Ct values do not necessarily reflect the disease severity of COVID-19 [ 8 ]. This could be particularly true for the elderly, in whom low levels of the virus may be sufficient enough to cause severe infection, especially when comorbidities, such as hypertension, diabetes or pulmonary diseases, are present [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further to the recognized risk factors for severity, the initial prognostic workup of persons infected by SARS-CoV-2 would also benefit from viral biomarkers able to predict COVID-19 evolution. In this regard, it is a current matter of debate whether SARS-CoV-2 viral load is an impactful factor in determining disease outcomes [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Previous evidence from SARS-CoV and influenza suggests that the higher the initial viral load, the worse the clinical evolution [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%